THE EFFECT OF USING PUPPET MEDIA ON THE ABILITY TO LISTEN TO STORIES IN CLASS II SD NEGERI 3 LENGKONG - Lista Febriany; Marlina Eliyana Simbolon; Pajar Anugrah Prasetio (Indonesian Journal of Elementary Teachers Education, 2023)
This study aims to determine the effect of the use of wayang media on the skills of listening to children's stories in class II SD Negeri 3 Lengkong. This research was conducted at SD Negeri 3 Lengkong from April to May 2023. The research method used in this study was a quasi-experimental design with a Non-Equivalent Control Group Design. Sampling was carried out using purposive sampling technique. The research sample for class B (experimental class) was a number of students. The instrument used in this research is an essay test. The data analysis technique used in this study was the normality test using the Kolmogrov-Smirnov test, homogeneity test using One Way Anova. Then proceed with testing the hypothesis using the T-test. The results of this study indicate that there is an effect of the use of wayang media on the skills of listening to children's stories in class II elementary school students. This is indicated by the results of statistical testing using the t test on the final test data (posttest) and it is known that Tcount 8.98 Ttable 1.69913, the hypothesis is accepted, meaning that there are differences in listening ability between classes using wayang media and classes using picture media , Based on the results of the N-Gain Test it is known that the results of the experimental class test before being given the wayang media treatment (Pretest) obtained an average value of 50.31. While the test results after being given the wayang treatment (posttest) was 83.75. Then obtain an N-Gain result of 0.71, then in accordance with the N-Gain criteria these results can be expressed as high criteria. While the test results in the control class which were carried out before using media images (pretest) obtained a value of 44. After being given the treatment it became 78. And obtained an N-Gain result of 0.64, according to the N-Gain criteria the result can be stated in the medium criteria. The conclusion is that there is a difference after it is proven in the N-Gain test. The experimental class with wayang treatment experienced a high increase compared to the control class which used image media.Keywords: Listening, quasi-experimental, instructional media, Wayang.